2009
DOI: 10.1093/annonc/mdp052
|View full text |Cite
|
Sign up to set email alerts
|

2008 SOR guidelines for the prevention and treatment of thrombosis associated with central venous catheters in patients with cancer: report from the working group

Abstract: Several rigorous studies do not support the use of anticoagulants for the prevention of CVC-associated thrombosis. Treatment of CVC-associated thrombosis relies on the same principles as those applied in the treatment of established thrombosis in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 43 publications
1
93
0
3
Order By: Relevance
“…In short-term central venous catheters, ultrasound guidance allows the operator to obtain an insertion site in a satisfactory location for proper securement, adequate room for dressing and taking into account the patient's comfort. Thus, adoption of ultrasound guidance may have a significant favourable impact on the risk of catheter contamination and catheterrelated infection [9, 15,53] and on the risk of catheterrelated venous thrombosis [62].…”
Section: Integration In Clinical Practicementioning
confidence: 99%
“…In short-term central venous catheters, ultrasound guidance allows the operator to obtain an insertion site in a satisfactory location for proper securement, adequate room for dressing and taking into account the patient's comfort. Thus, adoption of ultrasound guidance may have a significant favourable impact on the risk of catheter contamination and catheterrelated infection [9, 15,53] and on the risk of catheterrelated venous thrombosis [62].…”
Section: Integration In Clinical Practicementioning
confidence: 99%
“…A number of studies [9][10][11][12][13] have shown that realtime ultrasound guidance increases the rates of successful internal jugular catheterization by 100 % (particularly on the first pass). It also reduces the rates of mechanical complications (e.g., arterial puncture, hematoma, pneumothorax) as well as infectious and thrombotic events [15][16][17].…”
Section: Internal Jugular Veinmentioning
confidence: 99%
“…In 1986, Yonei et al [8] first described the use of real-time, two-dimensional ultrasound for cannulating the same vein. Since then, a number of studies [9][10][11][12][13][14] have demonstrated that real-time ultrasound guidance and, to a slightly lesser extent, ultrasound assistance markedly reduce the mechanical, infectious, and thrombotic complications of the central venous catheterization [15][16][17]. Compared with the conventional blind insertion, ultrasound assistance can also reduce the rates of catheterization failure and incorrect catheter placement, increase the likelihood of success at the first pass, shorten procedure times, and reduce costs.…”
Section: Introductionmentioning
confidence: 99%
“…The recommendations for prevention of CRT-related thrombosis by the French National Federation of Cancer Centers underline the importance of catheter positioning: the distal tip must be placed at the junction between the superior vena cava and the right atrium, and anticoagulant drugs are not recommended (14,15). Multiple studies have shown that the systematic use of low-molecular-weight heparin or long-term use of a vitamin K antagonist did not reduce the risk of thrombosis (6,(14)(15)(16).…”
mentioning
confidence: 99%